When I'm 75: College Students' Self Perceptions of the Challenges of Aging. (December 2020) - Hahn, Sarah J.; M. Kinney, Jennifer
Despite robust literature on people's attitudes toward aging, far less is known about attitudes toward one's own aging, especially among college students. We examined college students' self-perceptions of the challenges of aging using essays from a "When I'm 75" assignment implemented at the beginning and end of the semester in an introductory gerontology course. Interpretive Phenomenological Analysis was used to analyze 24 students' perceptions of their own aging at age 75. The superordinate theme, challenges of aging, was identified along with five subordinate themes: deterioration, age-related impairments, mental health, loneliness and loss, and experiencing ageism. Findings suggest that after completing the course, students both demonstrated an understanding of realistic age-related changes and had (contradictory) stereotypical ideas of what it would be like to be 75. Findings have implications for research that continues to evaluate self-perceptions and contributes to the development of pedagogical strategies and tools that promote students' optimal aging.